2024
DOI: 10.1039/d3ee03399f
|View full text |Cite
|
Sign up to set email alerts
|

An oxygen-coordinated cobalt single-atom electrocatalyst boosting urea and urea peroxide production

Shengbo Zhang,
Meng Jin,
Hui Xu
et al.

Abstract: Urea and urea peroxide play important role in agricultural and industrial production. The development of mild and efficient synthetic methods to achieve these two chemicals has aroused great attention, but...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…18 Remarkably, to date, to our best knowledge, only a scant few studies (around 21) have been published in the past three years related to urea electrosynthesis starting from NO 3 − and CO 2 . 29–52 These manuscripts provide a solid starting point for the research, but fundamental investigations are needed to clarify the steps that determine the most activity and selectivity: no direct experimental evidence has yet been reported showing the formation of intermediate species, but many DFT studies suggest that that pathway is energetically favourable for the formation of urea, at least on some electrocatalytic structures. For example Sargent et al showed by DFT calculation that the pathway seems to be favoured on Zn, rather than on Cu, in a ZnCu electrocatalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Remarkably, to date, to our best knowledge, only a scant few studies (around 21) have been published in the past three years related to urea electrosynthesis starting from NO 3 − and CO 2 . 29–52 These manuscripts provide a solid starting point for the research, but fundamental investigations are needed to clarify the steps that determine the most activity and selectivity: no direct experimental evidence has yet been reported showing the formation of intermediate species, but many DFT studies suggest that that pathway is energetically favourable for the formation of urea, at least on some electrocatalytic structures. For example Sargent et al showed by DFT calculation that the pathway seems to be favoured on Zn, rather than on Cu, in a ZnCu electrocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…39 On the other hand, an oxygen-coordinated cobalt single-atom electrocatalyst (Co–O–C) achieved a urea yield rate of 2704.2 ± 183.9 mg h −1 mg cat −1 due to reliable interactions between neighboring Co–(O–C 2 ) 4 sites promoted the C–N coupling for urea electrosynthesis. 46 Moreover, atomically dispersed nitrogen-coordinated single transition metal sites ( e.g. , Cu–N x –C) 35,37,60 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…5–7 Thus, to overcome this limitation, sacrificial agent oxidation reactions (SAORs) have been proposed as alternatives to OER. 8,9 Among them, urea oxidation reaction (UOR, CO(NH 2 ) 2 + 6OH − → N 2 + 5H 2 O + CO 2 + 6e − ) with a low theoretical potential of 0.37 V versus the reversible hydrogen electrode (RHE) is one of the ideal replacements, enabling a theoretical energy saving of ≈70%. 10–15 In addition, the use of urea-containing wastewater in UOR further demonstrates its significance.…”
Section: Introductionmentioning
confidence: 99%